Potential ecological risk from heavy metals in surface sediment of lotic systems in central region Peru - Custodio, María; Fow, Anthony; De la Cruz, Heidi; Chanamé, Fernán; Huarcaya, Javier (Frontiers in Water, 2024)
High Andean rivers are fragile ecosystems in the face of various threats, including heavy metal contamination. The objective of this study was to evaluate the potential ecological risk of heavy metals in surface sediment of lotic systems in the central region of Peru. The concentration of heavy metals in the sediment of the Chía river was in the following descending order: Fe > Mn > Zn > V > Pb > Cr > Ni > Cu > Mo > Hg, y en el río Miraflores fue: Fe > Mn > Zn > Ni > V > Cr > Cu > Pb > Hg > Mo. The mean concentration of Cu, Cr, Fe, Mn, Mo, Ni, Pb and V in the sediment samples in both rivers did not exceed the threshold values of the continental crust concentration, nor the interim sediment quality guidelines of the Canadian Council of Ministers of the Environment. However, the mean concentration of Hg exceeded the guideline values in the Miraflores river and the likely effect (0.7 mg.kg-1) adverse effects. The values of the enrichment factor (EF), contamination factor (CF), geoaccumulation index (Igeo) and pollution load index (PLI) indicated low contamination in the sediments of the rivers studied, being confirmed by the modified degree of contamination (mCd). Finally, the risk assessment showed that heavy metals in the sediments presented a low potential ecological risk.